Manifestasi citra alam dalam novel Ombak Bukan Penghalang: Suatu penelitian firasat Melayu - Zaitun, Hasan (2015)
Natural covering the entire life on the earth and sky. Prior to this study of literary materials such as poetry has been widely applied, especially the study of poems, rhymes and poems, but the study of the novel given less attention. Study aims to identify and analyze the use of natural elements in the novel by author Osman Ayob. In addition, analysis of this study will answer the question related to wether the image of nature that often used in the novel and how the image is used in the novel Ombak Bukan Penghalang. This study was analyzed by using a hunch Malay. Reseachers chose this approach because, Physiognomy as one of the approaches in the study off french literature (Hashim Awang, 1989). This study could explain that the artist Osman Ayob has made elements of nature as an important source of income their work.